Determinan Kejadian Hipertensi Di Rumah Sakit Umum Daerah Kabupaten Kaur Tahun 2021 - Nurlinda, Nurlinda; Diniarti, Fiya; Wulandari, Wulandari (Journal Hygeia Public Health, 2022)
The purpose of this study was to find out the determinants of the incidence of hypertension at the Kaur District General Hospital in 2021. This study used a Cross Sectional design, with an Accidental Sampling Technique with a sample of 76 respondents. The research instrument uses a questionnaire. The research analysis used univariate and bivariate analysis with the chi square test. The results of the study obtained that most of the respondents had an age at risk of 67.1%, most of the respondents had a family history of hypertension by 56.6%, almost some of the respondents had sufficient knowledge of 46.1%, most of the respondents were obese by 42 .1%, and most of the respondents experienced hypertension of 71.1% at the Kaur District General Hospital in 2021. Bivariate analysis obtained that there was a relationship between age, family history, knowledge, obesity, and the incidence of hypertension at the Kaur District Hospital in 2021 It is recommended to do regular exercise to avoid obesity, and a balanced diet for those who have a risky age and family history and increase understanding of hypertension to avoid risk factors for hypertension.